2020
DOI: 10.1136/archdischild-2019-318026
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of antimicrobial stewardship programmes in neonatology: a systematic review

Abstract: IntroductionAntimicrobial stewardship programmes (ASPs) are recommended to improve antibiotic use in healthcare and reduce antimicrobial resistance (AMR). Our aim was to investigate the effectiveness of ASPs in reducing antibiotic consumption, use of broad-spectrum/restricted antibiotics, antibiotic resistance and healthcare-associated infections (HAIs) in neonates.MethodsWe searched PUBMED, SCIELO, EMBASE and the Cochrane Database (January 2000–April 2019) to identify studies on the effectiveness of ASPs in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Due to differences in methodology in the available literature, it is difficult to compare our results with similar studies involving stewardship interventions in NICUs [16]. Existing studies were mostly performed in single NICUs, recruited mixed populations (some including both EOS and late onset sepsis [11], and did not select comparable inclusion criteria or outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Due to differences in methodology in the available literature, it is difficult to compare our results with similar studies involving stewardship interventions in NICUs [16]. Existing studies were mostly performed in single NICUs, recruited mixed populations (some including both EOS and late onset sepsis [11], and did not select comparable inclusion criteria or outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of contributing to AMR presents a challenge to prevention interventions such as intrapartum antibiotics and prophylaxis to prevent catheter-related infection 50. Antimicrobial stewardship programmes within neonatal units, principally reducing the initiation and duration of antibiotics, are supported by a growing body of observational evidence 51 52…”
Section: Discussionmentioning
confidence: 99%
“…Especially antimicrobial stewardship principles is of valuable interest to hospitalists caring of CMC as the prevalence of multidrug-resistant bacterial infections in children has significantly increased during the last two decades ( 54 ). CMC may receive many antibiotic treatments during their lifetime, and studies have shown that antimicrobial stewardship programs can be effectively applied in pediatric inpatient settings, e.g., neonatal care ( 55 ). Medical errors are estimated to be attributed in approximately 80% to communication breakdowns.…”
Section: Discussionmentioning
confidence: 99%